Iot Based Industrial Protection System with Energy Management - Revathi R, Aravind B, Deepak B, Kathiresan C (Mathematical Statistician and Engineering Applications, 2023)
Energy conservation can be done by energy auditing to reduce the consumption of energy in industries, etc. In industries, energy consumption and protection have been increased gradually. The evolution of the internet has become a major part of the advancement of technology with the help of sensors. Energy Management Systems are used to achieve high energy efficiency and give the consumer knowledge about the power consumption which is consumed over a period. The main functions of the management systems are in the generation, distribution, and transmission of power. Energy Management System is a platform that comprises both software and hardware that allows the consumer to monitor energy usage and control power consumption by increasing energy conservation. Monitoring and controlling of power can help the consumers to get the values of specific devices from the system.